Exogenous testosterone replacement therapy versus raising endogenous testosterone levels: current and future prospects - Khodamoradi, Kajal (F S Rev, 2020)
Testosterone replacement therapy is an important treatment option for men with low testosterone and symptomatic hypogonadism. Various formulations of exogenous testosterone replacement therapy exist, including oral, buccal, intramuscular, transdermal, subdermal, and nasal preparations. However, exogenous testosterone replacement therapy is a double-edged sword, posing risks to fertility due to negative feedback mechanisms on the hypothalamic-pituitary-gonadal (HPG) axis, which is the main regulator of testosterone production and spermatogenesis in males. Alternative pharmacologic therapies are being used to increase endogenous testosterone levels while attempting to preserve fertility and function of the HPG axis. These include selective estrogen receptor modulators, gonadotropins, and aromatase inhibitors. This review focuses on overviewing and comparing the currently available methods of exogenous testosterone replacement therapy, alternative treatments to increasing endogenous testosterone, and novel treatments that are currently under investigation to normalize testosterone levels while preserving the function of the HPG axis. In conclusion, reports suggest that, though Testosterone replacement therapy is an important way to restore testosterone levels and reduce symptoms associated with low testosterone, it is often difficult to decide which treatment to select for patients with testosterone deficiency. Several factors need to be considered to decide on optimal therapy option for the patient which include but are not limited to safety, efficacy, cost-effectiveness, dosing flexibility, and side effects. Alternative approaches which aim to improve endogenous testosterone production and preserve fertility are promising but still are at their initial stages of development. Ultimately, patient-centered decision making is paramount to appropriate treatment selection.